Insights on nitrogen/oxygen dual defects synergistic modulated charge transfer across the g-C3N4/TiO2-NTAs heterojunction enhanced photodegradation and gas-sensing performances - Zhufeng Shao; Lue Zhan; Yiman Zhang; Yonglong Zhang; Guoyang Yu; Yunfei Song; Xiaoming Xiu (Journal of Materials Research and Technology)
We report the successful synthesis of a highly ordered TiO2 nanotube array coated with a thin film of C3N4 nanoparticles using a straightforward hydrothermal-calcination approach. The resulting g-C3N4/TiO2-NTAs (CN/TONTs) nanohybrids exhibit significantly enhanced photoelectrochemical (PEC) photodegradation and gas-sensing capabilities when irradiated with UV–visible light. The PEC activity of these nanohybrids is notably superior to that of their semiconductor counterparts, primarily due to the synergistic coupling of strong heterojunction interfaces and abundant surface defects. Furthermore, nanosecond time-resolved transient photoluminescence and time-resolved fluorescence spectroscopy analyses suggest a coherent interfacial charge transfer mechanism, which elucidates the dominant dynamic processes within the CN/TONTs nanostructure. The optimized CN/TONTs-5 nanocomposite was observed to achieve a remarkable 98.3% photodegradation rate of methyl orange under UV–visible light excitation, which was found to outperform CN/TONTs-2 and CN/TONTs-8 by factors of 1.36 and 1.12, respectively. Furthermore, CN/TONTs-5 displays enhanced gas-sensing capabilities, exhibiting heightened sensitivity and accelerated response kinetics in comparison to CN/TONTs-2 and CN/TONTs-8.